Bingo capitalism : the law and political economy of everyday gambling - Bedford, Kate, 1975- (Oxford : Oxford University Press, 2019)
This work explores the legal and political history of bingo and how gender shapes, and is shaped by, gambling regulation. The author argues that bingo can provide new insight into three areas of political economy: more-than-capitalist' economies; the role of regulation in shaping those economies; and the gendered nature of that regulation.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 9, 2019).
Keywords: Bingo -- Law and legislation -- England; Bingo -- Law and legislation -- Wales; Bingo -- Economic aspects -- England; Bingo -- Economic aspects -- Wales; Law; Laws of specific jurisdictions & specific areas of law